PENGARUH PENGETAHUAN PRODUK, KEBERAGAMAN PRODUK DAN GAYA HIDUP TERHADAP LOYALITAS MEREK - Samsul Arifin; Mochamad Dimas Eka Saputra; Noviana Noviana; Sabila Aisyah Jamil; Rohmadhotin Fitri (Jurnal Baruna Horizon, 2023)
This research was conducted because it had the objective to determine the effect based on product knowledge, product diversity and lifestyle on brand loyalty. A quantitative approach is used for this study so that the research data is in the form of numbers. The analysis tool uses multiple linear regression which is supported by the SPSS version 26 application. The population is buyers of PT Siantar Top products domiciled in the city of Surabaya and the research sample is 100 respondents obtained based on a purposive sampling technique. Based on the research that has been done and from the results of testing the hypothesis, it can mean that there is a positive influence between product knowledge, product diversity, and lifestyle on brand loyalty. The hope is that in producing this healthy food, so that all people can consume these products so that consumers who are on a diet program will also feel the benefits and this can create brand loyalty because it meets consumer needs.